BEYOND STIGMA: UNDERSTANDING ASSOCIATIVE INTERACTIONS AMONG EX-LEPROSY PATIENTS IN SUMBERGLAGAH VILLAGE, MOJOKERTO REGENCY - Bagus Ratri Anggoro (International Journal of Medical Science and Public Health Research, 2024)
This study delves into the associative interactions among ex-leprosy patients in Sumberglagah Village, Mojokerto Regency, with a focus on understanding social dynamics beyond stigma. Through qualitative inquiry, including interviews and participant observation, the research explores how ex-leprosy patients navigate social relationships and construct supportive networks within their community. Findings reveal nuanced patterns of associative interactions, highlighting the resilience and agency of ex-leprosy patients in fostering social bonds and overcoming societal barriers. By shedding light on these dynamics, this study contributes to broader efforts aimed at promoting social inclusion and challenging stigmatization of individuals affected by leprosy.